SENI KRIYA ANTARA TEKHNIK DAN EKSPRESI - ., Rispul (CORAK, 2012)
The art craft is one of the traditional arts that could be used as an expression medium for anybody. With its capacity as an art filled of local genius, the art craft keep changing in every aspect, including on creating process and the medium has been used. Combination between technique and proper medium will create the art craft that capable to fulfill the worldâs need and demand. Craftsman capability to manage the medium, understanding it, created innovatively and to be able to see societyâs phenomenon will definitely generate responsibly work of art. Especially if they can took advantage of local genius that filled with sophisticated traditional value during their creating process, this will creates remarkable works of art craft which creative and innovative in a fresh form. Keywords: Art craft, technique, expression